Evaluation of sesame genotypes for resistance to root rot and oozing - GUPTA, R.B.L. (Indian Phytopathology, 2002)
Root rot caused by Macrophomina phaseolina (Tassi) Go id is an important disease of sesame (Sesamum indicum ) causing 5 to 100 per cent yield loss under field conditions. In Rajasthan, disease occurs over large area in western parts of the State and consequently loss in yield is quite high. Another important disease is oozing which occurs sporadically. It is characterized by oozing of gummy substance in the form of honey dew-like drops from all above ground parts of the plant which on drying give blackish appearance and eventually cause death of the plant much before crop maturity. The etiology of the disease is still obscure and no organism has been isolated from the diseased parts of the plant. The present investigation was undertaken with an objective to identify the genotype(s) promising to one or both the diseases under field conditions.